2021
DOI: 10.3390/cancers13061421
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Targeted Radionuclide Therapy Using [131I]ICF01012 in 3D Pigmented BRAF- and NRAS-Mutant Melanoma Models and In Vivo NRAS-Mutant Melanoma

Abstract: Purpose: To assess the efficiency of targeted radionuclide therapy (TRT), alone or in combination with MEK inhibitors (MEKi), in melanomas harboring constitutive MAPK/ERK activation responsible for tumor radioresistance. Methods: For TRT, we used a melanin radiotracer ([131I]ICF01012) currently in phase 1 clinical trial (NCT03784625). TRT alone or combined with MEKi was evaluated in three-dimensional melanoma spheroid models of human BRAFV600E SK-MEL-3, murine NRASQ61K 1007, and WT B16F10 melanomas. TRT in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, 3D models can be used to design targeted nuclear medicine therapy (e.g., effects of α or β labelled radiopharmaceuticals). Table 4 lists the recently developed radiopharmaceuticals using 3D models of various tumor types [54][55][56][57][58][59][60][61][62][63].…”
Section: Nuclear Medicine Therapymentioning
confidence: 99%
“…Furthermore, 3D models can be used to design targeted nuclear medicine therapy (e.g., effects of α or β labelled radiopharmaceuticals). Table 4 lists the recently developed radiopharmaceuticals using 3D models of various tumor types [54][55][56][57][58][59][60][61][62][63].…”
Section: Nuclear Medicine Therapymentioning
confidence: 99%
“…The radioactivity is delivered to a specific tumor by means of a systemic injection. For melanoma treatment, targeted treatment can be achieved by labeling small molecules, such as melanin ligands, peptides that recognize a specific receptor (MC1R), or antibodies (anti-melanin, anti-GD3) [365,366]. The efficacy of targeted radiotherapy depends on the dose delivered, which in turn depends on the radionuclide used and the time that the labeled compound remains associated with the target.…”
Section: Novel Structures and Drug Design Approachesmentioning
confidence: 99%
“…The mechanistic experiments revealed that the tolerance was a dominant immune escape mechanism while exhaustion was not detected after treatment with [ 131 I]ICF01012. Finally, the same researchers studied therapy with [ 131 I]ICF01012 alone or in combination with MEK inhibitors (MEKi) [ 69 ]. They utilized spheroidal and in vivo melanoma models that harbor constitutive MAPK/ERK activation thought to be responsible for tumor radioresistance.…”
Section: Targeting Melanin With Small Moleculesmentioning
confidence: 99%